AN INVESTIGATION INTO THE TEACHING OF SPEAKING SKILLS TO SECOND-DEGREE FRESHMEN AT NIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES, VIETNAM NATIONAL UNIVERSITY HANOI. : Nghiên cứu thực trạng dạy kĩ năng nói cho sinh viên năm thứ nhất loại hình đào tạo vă - Nguyễn, Thị Hà (ĐHNN, 2017)
48 p. + CD-ROM